TiO2 Based Photo-Catalysis for Virus Disinfection (Journal of Fiber Bioengineering and Informatics, 2023)
This review considers the current literature that is focused on the interface nanostructure/cell-wallmicroorganism to understand the annihilation mechanism. In this report, photocatalysis is discussedfor viral disinfection including TiO2 photocatalysis and other metal-containing photocatalysis. TiO2 based materials and its composites, metal-TiO2 systems, TiO2 heterojunction systems with other semiconductors, and TiO2 systems with graphene and other carbonaceous materials are discussed in detail.Some practical uses of titanium dioxide for photocatalytic disinfection processes for the effectiveprevention/eradication of microorganisms, considering the resistance that the microorganism coulddevelop without the appropriate regulatory aspects for human and ecosystem safety are also discussed.